Evaluation of the Entrepreneurial Printing School Program at SMKN 1 Tanjung Pinang Using CIPP Models - Said Thaha Ghafara; Ambiyar Ambiyar; Nizwardi Jalinus; Fahmi Rizal (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2023)
The purpose of this study was to analyze the implementation of the entrepreneurial school program from the aspect of evaluating context, input, process, and product (CIPP) with the existence of an entrepreneurial school program to support entrepreneurship subjects in vocational schools. The CIPP evaluation model is one type of model that can analyze the success rate of implementing the Entrepreneurial Printing School (SPW) program. The results of the evaluation analysis that have been carried out state that the SPW program at SMK Negeri 1 Tanjung Pinang based on the context aspect has a conducive environment to make the school a driving force for entrepreneurship, with the existence of creative products for students and teachers, has a business management department and a marketing department both retail and online. input from this program students starting from class X in various majors have been prepared to have an entrepreneurial spirit by making captains and danru in each class to carry out entrepreneurship programs and to support entrepreneurship subjects, teachers who teach entrepreneurship subjects are teachers who on average have businesses and have an entrepreneurial background and have good infrastructure, the process aspects of the activities are carried out in accordance with the guidebook that has been determined by the Directorate of Vocational Development (PSMK) and is carried out well, the product aspects are (1) Formation of the SPW team; (2) Socialization of the SPW program in the school environment; (3) SPW program product exhibition activities; (4) Fostering entrepreneurial activities; (5) Increasing student competence in digital marketing; (6) The creation of student entrepreneurial activities independently; and (7) Evaluation of the SPW continuation program.